Robotic Devices for Upper Limb Stroke Rehabilitation: Potential Research Trends - Radman, A; Ismail, W; Bahari, M (IEEE, 2024)
Upper limb rehabilitation plays an important role for stroke survivors to regain their functional abilities as much as possible after stroke. Robotic devices (RD) have been emerged as an effective intervention for upper limb rehabilitation in terms of consistency and reliability over repetitive exercises compared to the manual therapy intervention. In this paper, we present a literature survey on existing RD systems in perspective of performing thorough analysis to find potential research trends. Moreover, distinctive aspects and main shortages for various types of RD systems are provided. Based on this survey paper, although most researchers claimed that their RD systems improve upper limb functionality after stroke but there are still needs to make these systems more feasible.